Deciduous Tooth Eruption and Carpel Bone Ossification are two Methods used to Estimate a Person’s age that can be Compared for Forensic Purposes - Nadia Aslam, Raffat Rasool, Ishtiaque Ali Langah, Agha Shafique, Shahla Imran, Syed Asadyar Sadiq (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The ossification of the carpel bone in the hand and the emergence of deciduous teeth were both used to estimate a person’s age according to forensic standards. Study Design: Comparative study Place and Duration: Department of Forensic Medicine & Toxicology, LUMHS, Jamshoro, Sindh, Pakistan. July 2022-Feb 2023 Methods: A total of 110 children, both boys and girls, aged 3 to 14 years, participated in the study. The patients were equally split into two groups, each including 55 persons. Group I employed radioscopic (RVG) images of the left quadrant mandibular teeth to estimate age using the Demirjian technique, whereas Group II used a radiograph of the right wrist to estimate skeletal age using the Greulich and Pyle method. Disparities between chronological age and estimated skeletal and dental age were analyzed statistically. SPSS 22.0 was used to analyze all data. Results: There were majority males 55 (54.5%) in group I and 32 (58.2%) male cases in group II. In group I chronical age was 6.12±6.33 years and dental age was 5.75±8.63 years among patients of age group 3-8 years with difference 0.70±2.34 and patients of age group 9-14 years had chronical and dental age was 12.41±3.52 years and 11.16±2.67 with difference 0.72±1.29 while in group II chronical age and skeletal age among patients of age group 3-8 years was 8.02±3.42 years and 8.0±0.14 with difference 0.62±2.29 and patients of age group 9-14 years had chronical and skeletal age was 11.45±2.67 years and 10.90±0.93 with difference 0.60±1.22. With a p-value of >0.05, no difference was found between the two groups. Conclusion: Both dental and skeletal age estimation methods are reliable and accurate for determining a person’s age in a court of law, it has been determined. There was no discernible difference between the two approaches. Keywords: Bone Age (Greulich and Pyle), Forensic, Dental Age (Demirjian’s), Age Estimation